Enhancing Primary Students Scientific Literacy Through Virtual Laboratory-Based Digital Learning Packages to Support Sustainable Development Goals (SDGs) - Ummiatul Fitri; Aissy Putri Zulkarnaini; Gita Rahmi (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop and evaluate a virtual laboratory–based digital learning package to enhance scientific literacy among elementary school students. The study employed a Research and Development (R&D) approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The product was validated by experts in science education, media, and language, and then implemented with fourth-grade students. Data were collected through validation sheets, practicality questionnaires, and pretest–posttest instruments. The findings show that the developed learning package is both valid and practical for classroom use. Students demonstrated a significant improvement in scientific literacy, with an N-gain score of 0.65 (moderate category), particularly in understanding concepts, interpreting data, and relating science to everyday phenomena. The integration of interactive simulations and multimedia elements supported active engagement and meaningful learning experiences. Overall, the virtual laboratory–based digital learning package is effective in improving students’ scientific literacy and shows strong potential to enhance the quality of science instruction in primary education in line with 21st-century learning demands.